Exploring the relationship between communication and success of construction projects: the mediating role of conflict - Malik, Summaira (2022)
The success of a construction project is a widely discussed topic, even today, and there exists a difference of opinion. The impact of communication and conflict on project success is an important, but least addressed, issue in literature, especially in the case of underdeveloped countries. Miscommunication and conflict not only hinder the success of a project but also may lead to conflicts. The focus of this paper was to examine the impact of communication on project success with the mediating role of conflict. By using SPSS, demographics, descriptive statistics and correlation were determined. Smart PLS version 3.0 was used for confirmatory factor analysis (CFA), internal accuracy and validity estimates, hypothesis checking and mediation testing. The results showed that formal communication has a negative impact on the success of a construction project, resulting in conflicts among project team members, whereas informal communication and communication willingness have a positive impact on project success because people tend to know each other, and trust is developed. Task, process and relationship conflicts were used as mediating variables. It was found that task conflict effects the relations positively because project team members suggest different ways to do a certain task, and, hence, project success is achieved. On the contrary, process conflict and relationship conflict have a negative impact on communication and project success. Both of these conflicts lead to miscommunication, and project success is compromised. Hence, it is the responsibility of the project manager to enhance communication among project team members and to reduce the detrimental effects of process and relationship conflict on project success.